Macrostructure analysis of Indonesian-translation and source texts of the World Health Organization’s Covid-19 pandemic guidance - Risnawaty Risnawaty; Milisi Sembiring; Ihsan Fadilah; Henni Subagiarti; Annim Hasibuan (Universitas Pendidikan Indonesia, 2022)
Since the beginning of the Covid-19 Pandemic, the world has heavily relied on the internet to acquire information. The Pandemic is growing as a complex information discourse with so many texts from many sources. Various texts about Covid-19 certainly have various meanings for their readers. It is interesting to see an information resource that presents information in many languages in parallel. This study aims to reveal the global meaning of the parallel Indonesian and English texts of Covid-19 released by the World Health Organization. More specifically, this study examines whether parallelism in the two versions of the same text will present differences in the global meaning of each text; and whether there are social and political aspects that potentially affect the differences. The data for this study consists of two pairs of question-and-answer texts about Covid-19 published by WHO in English and Indonesian. This study used van Dijk's Critical Discourse Analysis framework at the macrostructure level. This study collected all texts and macro rules (deletion, generalization, and construction) have been applied to reduce information at the texts’ micro level to macropropositions at the macro level or the global topics/themes of discourse. There are some differences in the Indonesian text when compared to the original English text. Some of these differences may appear in the Indonesian translated version as a response to Indonesia's social and political conditions during the Covid-19 pandemic.